Three new species and one newly recorded species of oonopid spiders (Araneae: Oonopidae) from Hainan, China - Tong, Yanfeng; Li, Shuqiang (Zootaxa, 2009)
Three new species and one newly recorded species of the genera Gamasomorpha and Xestaspis collected from Hainan Island, China, are diagnosed, described and illustrated: Gamasomorpha comosa sp. nov., Gamasomorpha virgulata sp. nov., Xestaspis loricata (L. Koch, 1873) and Xestaspis rostrata sp. nov. The genus Xestaspis is firstly recorded from China. The type specimens are deposited in the Institute of Zoology, Chinese Academy of Sciences (IZCAS).